Design and Build a Web-Based CCTV Sales Information System: Rancang Bangun Sistem Informasi Penjualan CCTV Berbasis Web - Putra, Ryan Hanggara; Astutik, Ika Ratna Indra (Universitas Muhammadiyah Sidoarjo, 2022)
In this era of globalization, the use of computers and their systems has become a major requirement in order to improve performance in a company. The author made this Final Project based on research results from CV. Electronic Center. CV is a company engaged in the sale of electronic goods. The increasing sales at CV.Centra Elektronik then, problems arise that occur because the system is still manual. So it is necessary to create a web- based application system in order to be able to handle problems that arise in the sales process and at the same time increase the work and productivity of existing resources. Therefore the author designed a computerized data processing system of goods and sales starting from the process of inputting goods data, sales transactions and report generation.